Coping strategies in adolescence and labour-market participation in young adulthood: A prospective birth cohort study. Issue 5 (July 2020) - Billeskov, Lea; Labriola, Merete; Stabell, Cecilie L.; Dieckmann, Mathilde H.; Jensen, Nanna H.; Winding, Trine N.; Andersen, Johan H.; Lindholdt, Louise; Hansen, claus d.; Lund, Thomas
Aims: The aim of this study was to investigate whether coping strategies in adolescence (14–15 years of age) were associated with labour-market participation (LMP) in young adulthood (25–26 years of age) and whether the association differed by sex. Methods: A birth cohort from the former county of Ringkjoebing, Denmark, consisting of 2826 individuals, comprised the study population. In 2004, the study population completed a questionnaire from which information about coping and covariates were gathered. Coping strategies were measured using five sub-scales of the Brief COPE Scale, which were combined into two overall coping strategies: active coping and avoidant coping. Ten years later, the participants were followed for a 52-week period in a register on social benefits. Logistic regression was applied to data, with adjustment for covariates: sex, parents' socio-economic status (education and income) and self-rated health. Results: A total of 2203 (78%) participants were categorised as high LMP at follow-up. No significant associations were found between active coping in adolescence and LMP in 2014/2015. For avoidant coping, in the fully adjusted model, medium-level avoidant coping was associated with higher odds (odds ratio (OR)=1.02 (95% confidence interval (CI) 0.83–1.25) of high LMP. For low avoidant coping, the OR was 1.37 (95% 1.07–1.75). For both coping strategies, sex did not modify the association. Conclusions: Findings showed that avoidant coping was significantly associated with high LMP. Further research is needed to investigate coping in relation to specific problem areas.